2011
DOI: 10.1159/000334469
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Development of Peripheral Trigeminal Pathways in the Platypus <i>(Ornithorhynchus anatinus)</i> and Short-Beaked Echidna <i>(Tachyglossus aculeatus)</i>

Abstract: The extant monotremes (platypus and echidnas) are believed to all be capable of electroreception in the trigeminal pathways, although they differ significantly in the number and distribution of electroreceptors. It has been argued by some authors that electroreception was first developed in an aquatic environment and that echidnas are descended from a platypus-like ancestor that invaded an available terrestrial habitat. If this were the case, one would expect the developmental trajectories of the trigeminal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The 33 monotreme embryos, hatchlings, and juveniles (22 platypuses, Ornithorhynchus anatinus ; 11 short‐beaked echidnas, Tachyglossus aculeatus ) are held at the MfN or the AMNH and have been used in previous studies of the development of the monotreme nervous system and brainstem by our group (Ashwell, ; Ashwell et al, ; Ashwell and Hardman, ). The AMNH specimens had been kindly made available by Professor U. Zeller (previously of MfN).…”
Section: Methodsmentioning
confidence: 99%
“…The 33 monotreme embryos, hatchlings, and juveniles (22 platypuses, Ornithorhynchus anatinus ; 11 short‐beaked echidnas, Tachyglossus aculeatus ) are held at the MfN or the AMNH and have been used in previous studies of the development of the monotreme nervous system and brainstem by our group (Ashwell, ; Ashwell et al, ; Ashwell and Hardman, ). The AMNH specimens had been kindly made available by Professor U. Zeller (previously of MfN).…”
Section: Methodsmentioning
confidence: 99%
“…The 31 monotreme embryos, hatchlings and juveniles (21 platypuses, Ornithorhynchus anatinus ; 10 short‐beaked echidnas, Tachyglossus aculeatus ) are held at the MfN or the AMNH and have been used in previous studies of the development of the monotreme nervous system and brainstem by our group (Ashwell and Hardman, ; Ashwell et al, ). The AMNH specimens had been kindly made available by Professor U Zeller, formerly of MfN.…”
Section: Methodsmentioning
confidence: 99%
“…Manger et al [1998b] have reported that electroreceptors begin to emerge on the surface of the platypus bill around 10 days after hatching, but they did not have the opportunity to examine sections of pre-hatching platypus. We recently showed that the peripheral trigeminal pathways of platypus and echidna are morphologically distinct from the earliest stages of the skin receptor, trigeminal nerve and ganglion differentiation, even before hatching [Ashwell et al, 2012]. In the case of the peripheral receptors, distinctive features of the two species emerge during the last third of incubation, but differences in the size of the trigeminal ganglion are evident even earlier, by the first third of incubation.…”
Section: Evolutionary Considerations Of the Timing And Process Of Trimentioning
confidence: 98%